Methylation at the C-3′ in D-Ring of Strigolactone Analogs Reduces Biological Activity in Root Parasitic Plants and Rice - Jamil, Muhammad; Kountche, Boubacar A.; Haider, Imran; Wang, Jian You; Aldossary, Faisal; Zarban, Randa A.; Jia, Kun-Peng; Yonli, Djibril; Shahul Hameed, Umar F.; Takahashi, Ikuo; Ota, Tsuyoshi; Arold, Stefan T.; et al. (Frontiers in Plant Science, 2019)
Strigolactones (SLs) regulate plant development and induce seed germination in obligate root parasitic weeds, e.g. Striga spp. Because organic synthesis of natural SLs is laborious, there is a large need for easy-to-synthesize and efficient analogs. Here, we investigated the effect of a structural modification of the D-ring, a conserved structural element in SLs. We synthesized and investigated the activity of two analogs, MP13 and MP26, which differ from previously published AR8 and AR36 only in the absence of methylation at C-3'. The de-methylated MP13 and MP26 were much more efficient in regulating plant development and inducing Striga seed germination, compared with AR8. Hydrolysis assays performed with purified Striga SL receptor and docking of AR8 and MP13 to the corresponding active site confirmed and explained the higher activity. Field trials performed in a naturally Striga infested African farmer’s field unraveled MP13 as a promising candidate for combating Striga by inducing germination in host’s absence. Our findings demonstrate that methylation of the C-3' in D-ring in SL analogs has a negative impact on their activity and identify MP13 and, particularly, MP26 as potent SL analogs with simple structures, which can be employed to control Striga, a major threat to global food security.